Determinants of financial information disclosure: A visualization test by cognitive mapping technique - Nassreddine, Garoui (2016)
The purpose of this paper is to examine determinants of financial information disclosure by Tunisian companies. The methodology is based on qualitative approach, using the cognitive mapping technique. To take into account the specificities of the Tunisian economic, we felt that it is essential to conduct a qualitative analysis in the light of which we can identify the factors motivating the disclosure of financial information. The qualitative analysis is based on the census via a set of cases carried outin several Tunisian companies to understand their perceptions regarding the determinants of financial disclosure. Doi: https://doi.org/10.1016/j.jefas.2016.03.002